A methodological approach to upscale organic and agroecological – local agrifood systems: the case of the Pampa Organica Norte group in Argentina - Sciurano, Juan Pablo; Arfini, Filippo; Maccari, Michele (Frontiers in Sustainable Food Systems, 2024)
Organic Agriculture and Agroecology are production systems considered relevant for building up sustainable food systems at an environmental, social and economic level. In recent years there has been a growing interest in considering which processes can contribute to upscaling these systems. At a global level Agroecological Local Agri-food Systems and Bio-districts are becoming beacons for that purpose. This paper presents a case study of an organic and agroecological group of producers in the Argentinian Pampa Region where we used the Participatory Action Research (PAR) approach in implementing three interconnected methodologies: (i) Sustainability assessment using the FAO Tool for Agroecology Performance Evaluation (TAPE), (ii) Participatory Value chain Development and (iii) Stakeholder Analysis. This was done to verify if the combination of methodologies can be useful to (i) evaluate the current situation of the group in terms of LAFS development and (ii) identify which possible activities would be required for upscaling organic and agroecological practices at a regional level with a neo-endogenous approach. We conclude that the participative assessment implemented was useful to identify the group stage in terms of LAFS development and also to identify the activation requirements for upscaling the system at the same time that the participatory process addressed and organized a set of procedures in the hands of the group for implementing that process.